Transforming Islamic School Management to Address Parental Preferences in the Digital Era: Transformasi Manajemen Sekolah Islam untuk Memenuhi Preferensi Orang Tua di Era Digital - Wildan Miftahussurur; Fian Abrori; Moh. Rifqi Wildan Firdaus; Maripaz C. Abas (Mapendis: Jurnal Manajemen Pendidikan Islam, 2025)
Islamic boarding schools (pesantren) are value-based educational institutions in which tradition and religious authority play a decisive role in shaping institutional governance. While previous studies have highlighted the historical and cultural significance of pesantren, less attention has been paid to how authority structures influence management change within these institutions. This study explores patterns of authority and institutional decision-making in Islamic boarding school education, focusing on the ways tradition mediates managerial transformation. Using a qualitative research design, data were collected through in-depth interviews, participant observation, and document analysis in selected Islamic boarding schools undergoing organizational change. The findings show that authority in pesantren operates through layered and relational structures rather than formal bureaucratic hierarchies. Decision-making is characterized by consultative practices, moral legitimacy, and symbolic leadership, particularly centered on the role of the kiai. Management change is not implemented through procedural enforcement alone but is negotiated through existing authority networks and value-based frameworks.The study further reveals that tradition functions as a managerial resource that enables pesantren to balance institutional continuity with adaptation to external demands. Formal management structures coexist with informal authority practices, resulting in a hybrid governance model that accommodates accountability requirements without undermining institutional identity. These findings challenge linear and technocratic models of educational reform and underscore the importance of context-sensitive governance in religious educational institutions. This study contributes to educational management literature by positioning tradition and moral authority as analytical variables in understanding institutional change within Islamic education.